Ceramic planar waveguide laser of non-aqueous tape casting fabricated YAG/Yb:YAG/YAG - Wang, Chao (Sci Rep, 2016)
Ceramic YAG/Yb:YAG/YAG planar waveguide lasers were realized on continuous-wave and mode-locked operations. The straight waveguide, fabricated by non-aqueous tape casting and solid state reactive sintering, enabled highly efficient diode-pumped waveguide continuous-wave laser with the slope efficiency of 66% and average output power of more than 3 W. The influence of the waveguide structure on the wavelength tunability was also experimentally investiccgated with a dispersive prism. Passively mode-locked operation of the ceramic waveguide laser was achieved by using a semiconductor saturable absorber mirror (SESAM), output 2.95 ps pulses with maximum power of 385 mW at the central wavelength of 1030 nm.